How New Is the New Testament? : First-Century Judaism and the Emergence of Christianity - Hagner, Donald A. 1936- (Baker Academic, 2018)
What is so new about the New Testament? Senior scholar Donald Hagner tackles the issue of how distinct early Christianity was from the first-century Judaism from which it emerged. He surveys newness in the entire New Testament canon, examining the evidence for points of continuity and discontinuity between formative Judaism and early Christianity. Hagner's accessible analysis of the New Testament text shows that despite Christianity's thorough Jewishness, from the beginning dramatic newness was an essential aspect of this early literature.